Evaluation of the Perceived Barriers and Facilitators to Timely Extubation of Critically Ill Adults: An Interprofessional Survey. Issue 3 (8th February 2021) - Balas, Michele C.; Tate, Judith; Tan, Alai; Pinion, Brennon; Exline, Matthew
Abstract: Background: Spontaneous breathing trials (SBTs) are an evidence‐based way of identifying patients ready for mechanical ventilation (MV) liberation. Despite their effectiveness, global SBT performance rates remain suboptimal, and many patients who demonstrate the ability to breathe on their own remain on MV. The factors that influence clinicians' decision to discontinue MV following a successful SBT remain unclear. Aims: The aim of this study was to explore the underlying causes of extubation delays in the intensive care unit (ICU) from an interprofessional perspective. Methods: An exploratory, descriptive, cross‐sectional design was used. An online survey was administered in December 2019 to clinicians practicing in three ICUs at a single medical center in the U.S. Survey questions focused on clinicians' perceptions of current MV liberation practices and perceived barriers or facilitators to timely extubation after a successful SBT. Results: Of 425 eligible clinicians, 135 completed the survey (31.7% response rate). The majority of clinicians believed the current SBT and extubation process took too long ( n  = 108; 80.0%) and that this delay negatively affected patient outcomes. While professional groups differed in their rankings of importance, factors perceived to contribute to extubation delays most commonly included SBT timing, low provider confidence levels in making extubation decisions, and patient‐specific factors. Potential strategies to overcome these barriers included developing an automated extubation protocol, performing SBTs when the provider responsible for final extubation decisions is physically present, and decreasing clinician perception of reprimand or condemnation for failed extubations. Linking Evidence to Action: The MV liberation process is complex and dependent on the decisions of various ICU professionals. Clinicians perceive a number of potentially modifiable provider‐ and organizational‐level factors that cause extubation delays in everyday practice. Understanding and addressing these barriers is essential for improving ICU quality and patient outcomes. Future research should explore the effect of nurse and respiratory therapist‐driven extubation protocols on MV liberation rates.